A Model for Better Leveraging the Point of Preoperative Assessment: Patients and Providers Look Beyond Operative Indications When Making Decisions. Issue 8 (15th April 2016) - Nelson, Olivia; Quinn, Timothy D.; Arriaga, Alexander F.; Hepner, David L.; Lipsitz, Stuart R.; Cooper, Zara; Gawande, Atul A.; Bader, Angela M.
Abstract : Previous literature on preoperative evaluation focuses on the impact on the day of surgery cancellations and delays; however, the framework of cancellations and delays at the time of the elective outpatient preoperative anesthesia visit has not been categorized. We describe the current model in the preoperative clinic at Brigham and Women's Hospital, examining the pattern of cancellations at the time of this preoperative visit and the framework used for categorizing the issues involved. Looking at this broader framework is important in an era of patient-centered care; we seek to identify targets to modify the preoperative assessment and adequately assess and capture the spectrum of issues involved. Elective cases evaluated in the preoperative clinic were reviewed over 10 months. Characteristics of cancelled and noncancelled cases were compared. In-depth analysis of issues related to cancellation was done; 1-year follow-up was completed. Cancellation patterns included categories encompassing clinical, financial, alignment with patient values and goals, compliance, and social issues. The period of preoperative assessment can therefore be leveraged to review a number of domains that can adversely affect surgical outcomes and improve patient-centered care. Also, our framework allows the institution to benchmark these patterns over time; increases in cancellations at the time of the preoperative anesthesia clinic visit for specific categories can prompt an opportunity to examine and improve preoperative workflow.